IMPLEMENTASI KEBIJAKAN KESEHATAN “LIBAS 2+” SEBAGAI UPAYA MENURUNKAN ANGKA KEMATIAN IBU DAN BAYI DI KABUPATEN SAMPANG - Ali Imron (Center for Health Policy and Management, 2013)
Introduction: The issue of MDGs 4 and 5 that targets reducingthe AKI and AKB by three-quarters between 1990 and 2015seems difficult to achieve if there are no immediate concretesteps. Areas with the highest AKI and AKB are SampangRegency. Looking at the empirical conditions, it is necessary toidentify the factors that led to the high AKI and AKB in SampangRegency. There is an existing health policy in Sampang districtthrough LIBAS (Lima Bebas) 2+, but it needs to be monitoredand evaluated to ensure policy implementation went well. Thisstudy aims to assess the implementation of the Libas programsand identify socio-cultural factors that influence health policyimplementation.Methods: This study used qualitative methods that took placeat the Puskesmas Camplong, Sampang Regency. Informantswere selected purposively. The research data was collectedby participating observation, in-depth interviews, and focusgroup discussions. The finding was analyzed using descriptiveanalysis.Results: Sociologically, the implementation of policy to reduceAKI and AKB in Sampang Regency is one of which is influencedby the shaman midwife partnerships, especially in the deliveryprocess. Increasing public confidence in midwives indicatesstrengthening social relations. 5T programs (weigh, tension,tablet Fe, weigh abdominal size, and height) is helpful to controlthe development of maternal pregnancy. “Healthy Babies 24Hours” SMS number serves as a control and monitoring indelivery care. Nonetheless, culturally, traditional culturalconstruction of Madura, particularly the coastal communities,still entrenched so that the construction of knowledge aboutreproductive health is still weak. Shaman massage, herbalmedicine, pregnancy myths, and charismatic central figureare prominent. Social relation between local actors is still weak,so is the local actors support.Conclusion: Strong local culture values and weak socialrelationship and support of local actors as a result of programimplementation LIBAS2+ reduce AKI and AKB efforts inSampang Regency had not been effective.Keywords: health policy, LIBAS 2+, social relationship, localculture